Cell phones answer Internet's call. - Sweet, W. (IEEE spectrum)
Cellular service providers, handset manufacturers, and system integrators are captivated by the promise of the wireless Internet using third generation cellular telephony. The leading contender to be the global standard for third-generation cellular telephony is the Universal Mobile Telecommunication System (UMTS). This is a wideband CDMA system designed to be smoothly backward-compatible with GSM, and also the leading member of the IMT-2000 family of third-generation systems sponsored by the International Telecommunication Union (ITU). The developments of this technology and its impact on the telecommunications industry worldwide are discussed